Isolasi dan Aktivitas Antibakteri Aktinomisetes Asal Tanah Gambut Riau - Linda, Tetty Marta; Roza, Rodesia Mustika; Yuliati, Rola; Wahyuliyanti, Wahyuliyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2007)
The aims of this study are to isolate actinomycetes from peat soil samples, to determine the ability of actinomycetes to inhibit the growth of Gram positive bacteria (Bacillus subtilis and Staphylococcus aureus) and Gram negativebacteria (Escherichia coli and Pseudomonas sp.). A total of 14 actinomycetes strains were recovered from peat soil samples using pour plate method with Starch Casein Agar. The results showed that 11 isolates were active against B. subtilis, 8 isolates against S. aureus, 8 isolates were active against E. coli and 8 isolates againstPseudomonas sp. Two isolates (SM 1.3 and SM 1.6) were active against all bacterial targets.